Resin composition and application thereof

By combining modified maleimide resin, cyanate compounds, epoxy resin, high Dk titanate inorganic filler and high thermal conductivity of nitride inorganic filler in the resin composition, and using fillers of different shapes, The problem of difficult to take into account both the dielectric constant and thermal conductivity of the substrate material in the prior art is solved, and a resin composition with high dielectric constant, high thermal conductivity and high peel strength is realized, which is suitable for high heat resistance and high frequency antenna substrate modules.

CN119391182APending Publication Date: 2025-02-07SHENGYI TECH SUZHOU
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411505187.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The prior art has contradictions in improving the dielectric constant and thermal conductivity of substrate materials. Titanate compounds have poor thermal conductivity and high dielectric constant. On the contrary, the dielectric constant of high thermal conductivity fillers is low, making it difficult to meet the high dielectric at the same time. Electricity constant and high thermal conductivity requirements.

Method used

A resin composition is adopted, including modified maleimide resin, cyanate compounds, epoxy resin, high Dk titanate inorganic filler and high thermal conductivity of nitride inorganic filler, and is combined with fillers of different shapes. Improve the filling amount and dispersion of the filler.

Benefits of technology

On the basis of meeting high heat resistance, the thermal conductivity and dielectric constant of the resin composition are improved, and the peel strength is enhanced. It is suitable for high heat resistance and high frequency antenna substrate modules, especially to meet the requirements of millimeter wave antenna modules.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005104033190000061
    Figure BDA0005104033190000061
  • Figure BDA0005104033190000121
    Figure BDA0005104033190000121
  • Figure BDA0005104033190000122
    Figure BDA0005104033190000122
Patent Text Reader

Abstract

The invention provides a resin composition and application thereof. The resin composition comprises the following components in parts by weight: 50-100 parts of modified maleimide resin; 5-50 parts by weight of a cyanate ester compound; 0-60 parts by weight of epoxy resin; 10-100 parts by weight of a first filler, wherein the Dk of the first filler under 10GHz is 10 or more; 1-150 parts by weight of a second filler, wherein the thermal conductivity of the second filler is more than 15W / m.K; one of the first filler and the second filler is of a spherical structure, and the other one is of a non-spherical structure; a high-Dk (dielectric constant) first filler and a high-heat-conductivity second filler are added into a high-heat-resistance bismaleimide resin-cyanate curing system, so that the heat conductivity and the Dk value of the resin composition are further improved on the basis of meeting higher heat resistance; meanwhile, the first filler and the second filler are arranged in different shapes and are matched for use, so that the filling amount of the filler in the resin composition can be increased, the heat conductivity and the Dk value can be inhibited from being reduced, and the peel strength can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electronic materials, and in particular to a resin composition and application thereof. Background Art

[0002] In recent years, as electronic equipment or electrical equipment develops towards high speed, thinness, miniaturization, high integration and high thermal conductivity, the installation density of electronic components on printed circuit boards has increased, and the heat inside electronic equipment has increased year by year. The heat dissipation performance of the carrier of electronic components - substrate materials is becoming more and more important, especially in copper-clad laminates suitable for high-frequency and high-speed circuits. At the same time, since portable terminals such as smart phones require miniaturization, in order to achieve the miniaturization of antenna modules, it is necessary to increase the dielectric constant (Dk) of the substrate.

[0003] In terms of high dielectric constant, the prior art increases the dielectric constant of substrate materials by adding high dielectric constant fillers, and often uses titanates. However, the thermal conductivity of titanate compounds is poor, and it is difficult to meet the heat dissipation requirements in high-layer and high-integration components. In addition, the dispersibility of titanate compounds in thermosetting resin materials is poor, and the amount added is limited. In terms of high thermal conductivity, the prior art often uses high thermal conductivity fillers such as aluminum oxide, silicon nitride, and boron nitride, but these fillers have low dielectric constants and are difficult to apply in the field of antenna modules. High thermal conductivity fillers seriously affect the dielectric constant of substrate materials. Summary of the invention

[0004] The purpose of the present invention is to provide a resin composition and application thereof.

[0005] To achieve the above-mentioned purpose, the present invention adopts the following technical scheme: a resin composition, comprising:

[0006] Modified maleimide resin: 50-100 parts by weight;

[0007] Cyanate compound: 5-50 parts by weight;

[0008] Epoxy resin: 0-60 parts by weight;

[0009] First filler: 10-100 parts by weight, wherein the Dk of the first filler at 10 GHz is greater than 10;

[0010] Second filler: 1-150 parts by weight, the thermal conductivity of the second filler is greater than 15 W / mK;

[0011] One of the first filler and the second filler is a spherical structure, and the other is a non-spherical structure.

[0012] As a further improvement of the present invention, the first filler is a titanate inorganic filler; or, the first filler is a titanate inorganic filler, and the titanate inorganic filler is selected from at least one of calcium titanate, strontium titanate, barium titanate, lead titanate, magnesium titanate, lead zirconate titanate, and lanthanum lead zirconate titanate.

[0013] As a further improvement of the present invention, the second filler is an inorganic nitride filler; or, the second filler is an inorganic nitride filler, and the inorganic nitride filler is selected from at least one of aluminum nitride, boron nitride, and silicon nitride.

[0014] As a further improvement of the present invention, the first filler is an inorganic filler surface-treated with a silane coupling agent; and / or the second filler is an inorganic filler surface-treated with a silane coupling agent.

[0015] As a further improvement of the present invention, the average particle size of the first filler is 0.1 μm-5 μm; the average particle size of the second filler is 3 μm-25 μm.

[0016] As a further improvement of the present invention, the average particle size of the first filler is smaller than the average particle size of the second filler.

[0017] As a further improvement of the present invention, the cyanate ester compound is selected from at least one of bisphenol A type cyanate ester compounds, bisphenol F type cyanate ester compounds, bisphenol E type cyanate ester compounds, bisphenol M type cyanate ester compounds, DCPD type cyanate ester compounds, naphthalene type cyanate ester compounds, biphenyl type cyanate ester compounds, and triphenyl type cyanate ester compounds.

[0018] As a further improvement of the present invention, the modified maleimide resin is at least one of allyl-modified maleimide resin, aromatic diamine-modified maleimide resin, aliphatic diamine-modified maleimide resin, and aminophenol-modified maleimide resin.

[0019] As a further improvement of the present invention, the epoxy resin is selected from at least one of the following structures:

[0020] Wherein, p is an integer from 1 to 20;

[0021] Wherein, n is an integer from 1 to 20;

[0022] Wherein, m is an integer from 0 to 20;

[0023] Wherein, n is an integer from 1 to 20;

[0024] Wherein, n is an integer of 1-20.

[0025] To achieve the above-mentioned object of the invention, the present invention also provides a use of the above-mentioned resin composition in prepregs, copper-clad laminates, insulating films, insulating boards, circuit substrates and electronic devices.

[0026] Beneficial effects: Compared with the prior art, the present invention has the following advantages:

[0027] In the present invention, a first filler with high Dk (dielectric constant) and a second filler with high thermal conductivity are added to a high heat-resistant bismaleimide resin-cyanate ester curing system, and the first filler with high Dk (dielectric constant) and the second filler with high thermal conductivity are used in combination, so that the resin composition further improves the thermal conductivity and Dk value on the basis of meeting the higher heat resistance; at the same time, the first filler and the second filler are set to different shapes and used in combination with each other, which can increase the filling amount of the filler in the resin composition, inhibit the decrease of thermal conductivity and Dk value, and improve the peel strength, so as to obtain a resin composition with excellent high heat resistance, high Dk, high peel strength and high thermal conductivity, so as to finally obtain a cured product with high heat resistance, high thermal conductivity, high dielectric constant and high peel strength, so as to obtain a cured product with relatively excellent comprehensive performance, which can be well applied in the field of high heat-resistant high-frequency antenna substrate modules, especially can meet the requirements of millimeter wave antenna modules. DETAILED DESCRIPTION

[0028] The following is a specific implementation of the embodiment of the present invention. It should be pointed out that for ordinary technicians in this field, several improvements and modifications can be made without departing from the principles of the embodiment of the present invention. These improvements and modifications are also considered to be within the scope of protection of the embodiment of the present invention.

[0029] The terms “comprising” and “containing” in the present specification mean that other components may be contained in addition to the components mentioned above, and these other components can impart different characteristics to the resin composition.

[0030] The present invention provides a resin composition, comprising:

[0031] Modified maleimide resin: 50-100 parts by weight;

[0032] Cyanate compound: 5-50 parts by weight;

[0033] Epoxy resin: 0-60 parts by weight;

[0034] First filler: 10-100 parts by weight, wherein the Dk of the first filler at 10 GHz is greater than 10;

[0035] Second filler: 1-150 parts by weight, the thermal conductivity of the second filler is greater than 15 W / mK;

[0036] One of the first filler and the second filler is a spherical structure, and the other is a non-spherical structure.

[0037] The resin composition of the present invention adds a first filler with a high Dk (dielectric constant) and a second filler with a high thermal conductivity to a high heat-resistant bismaleimide resin-cyanate ester curing system, and the first filler with a high Dk (dielectric constant) and the second filler with a high thermal conductivity are used in combination, so that the resin composition further improves the thermal conductivity and the Dk value on the basis of meeting the higher heat resistance; at the same time, the first filler and the second filler are set to different shapes and used in combination with each other, which can increase the filling amount of the filler in the resin composition, inhibit the decrease of the thermal conductivity and the Dk value, and improve the peel strength, so as to obtain a resin composition with excellent high heat resistance, high Dk, high peel strength and high thermal conductivity, so as to finally obtain a cured product with high heat resistance, high thermal conductivity, high dielectric constant and high peel strength, so as to obtain a cured product with relatively excellent comprehensive performance, which can be well applied in the field of high heat-resistant high-frequency antenna substrate modules, especially can meet the requirements of millimeter wave antenna modules.

[0038] It should be noted that the cured product in the present invention can be understood as a prepreg, an insulating film, an insulating board, a copper-clad laminate, a circuit substrate, an electronic device, and the like.

[0039] Specifically, the above-mentioned non-spherical structure includes an angular shape, a plate shape, a needle shape or an amorphous shape.

[0040] In a specific embodiment, the first filler is a titanate inorganic filler, and the second filler is a nitride inorganic filler. When the titanate inorganic filler is a spherical structure, the nitride inorganic filler is a non-spherical structure; when the titanate inorganic filler is a non-spherical structure, the nitride inorganic filler is a spherical structure.

[0041] Specifically, the titanate inorganic filler is selected from at least one of calcium titanate, strontium titanate, barium titanate, lead titanate, magnesium titanate, lead zirconate titanate, and lanthanum lead zirconate titanate.

[0042] The nitride inorganic filler is selected from at least one of aluminum nitride, boron nitride and silicon nitride.

[0043] In some optional embodiments, the average particle size of the first filler is smaller than the average particle size of the second filler, that is, the first filler and the second filler of different shapes, types and particle sizes are mixed and applied to the resin composition, and the high Dk filler with smaller particle size will be dispersed into the high thermal conductivity fillers with larger particle size, which can improve the thermal conductivity of the substrate. At the same time, the high Dk filler is evenly dispersed and the decrease of the Dk value of the resin composition is suppressed, so as to obtain a resin composition with high thermal conductivity and a high level of Dk value. It can also increase the filling amount of the filler in the resin composition, maintain the excellent dispersibility of the filler, so that the resin composition has excellent high dielectric constant and high thermal conductivity. At the same time, it can be well used in the field of high heat-resistant high-frequency antenna substrate modules in combination with high heat-resistant resins to meet the high heat resistance, high Dk value and high thermal conductivity of 5G millimeter wave antenna modules.

[0044] Specifically, the average particle size of the first filler is 0.1μm-5μm, such as 0.1μm, 1μm, 2μm, 3μm, 4μm, 5μm and specific point values ​​between the above-mentioned values. Due to space limitations and simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range; the average particle size of the second filler is 3μm-25μm, such as 3μm, 5μm, 10μm, 15μm, 20μm, 25μm and specific point values ​​between the above-mentioned values. Due to space limitations and simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0045] In some optional embodiments, at least one of the first filler and the second filler is surface treated with a silane coupling agent. Preferably, a silane coupling agent containing a reactive group is used to improve the dispersibility of the filler mixture.

[0046] Specifically, the titanate inorganic filler is a titanate inorganic filler surface-treated with a reactive group-containing silane coupling agent, which can improve the dispersibility of the titanate inorganic filler. The nitride inorganic filler is a nitride inorganic filler surface-treated with a reactive group-containing silane coupling agent, which can improve the dispersibility of the nitride inorganic filler.

[0047] Specifically, the silane coupling agent is selected from at least one of a vinyl silane coupling agent, an epoxy silane coupling agent, an amino silane coupling agent, and a methacrylate silane coupling agent.

[0048] Preferably, the silane coupling agent uses a silane coupling agent with the following structural formula:

[0049]

[0050] After the titanate inorganic filler and the nitride inorganic filler are surface treated with the silane coupling agents corresponding to the above four structural formulas, the vinyl or amino group in the silane coupling agent undergoes a cross-linking reaction with the maleimide group, so that the titanate inorganic filler and the nitride inorganic filler are more easily introduced into the resin curing system, so that the dispersibility of the titanate inorganic filler and the nitride inorganic filler in the resin composition is relatively excellent, and no adverse phenomena such as agglomeration and resin agglomeration occur, thereby being able to inhibit the decrease in the dielectric constant and thermal conductivity of the resin composition.

[0051] Specifically, the surface treatment method of the titanate inorganic filler and the nitride inorganic filler using the silane coupling agent can adopt existing surface treatment methods, such as dry method, adsorption method, chemical reaction method, polymerization method, gas phase surface treatment method, etc., which are not specifically explained here.

[0052] Furthermore, the cyanate compound is a monomer, a prepolymer or a mixture thereof.

[0053] In some optional embodiments, the cyanate ester compound is selected from at least one of bisphenol A-type cyanate ester compounds, bisphenol F-type cyanate ester compounds, bisphenol E-type cyanate ester compounds, bisphenol M-type cyanate ester compounds, DCPD-type cyanate ester compounds, naphthalene-type cyanate ester compounds, biphenyl-type cyanate ester compounds, and triphenyl-type cyanate ester compounds.

[0054] Furthermore, the modified maleimide resin is at least one of an allyl-modified maleimide resin, an aromatic diamine-modified maleimide resin, an aliphatic diamine-modified maleimide resin, and an aminophenol-modified maleimide resin.

[0055] The aromatic diamine compound in the aromatic diamine-modified maleimide resin is at least one of substituted phenylenediamine, methylphenylenediamine, dimethylphenylenediamine, trimethylphenylenediamine, tetramethylphenylenediamine, xylene diamine, diaminopyridine, diaminodiphenylmethane, substituted diaminodiphenylmethane, bis[4-(4-aminophenoxy)phenyl]propane, bis[4-(4-aminophenoxy)phenyl]hexafluoropropane, diaminobenzophenone, diaminodiphenyl ether, diaminodiphenyl sulfone, diaminobiphenyl, diaminodiphenyl sulfide, diaminobinaphthyl, diaminodiphenylfluorene, and diaminoanthraquinone.

[0056] The aliphatic diamine compound in the aliphatic diamine-modified maleimide resin is selected from one or more of dimethylenediamine, tetramethylenediamine, pentamethylenediamine, hexamethylenediamine, heptamethylenediamine, octamethylenediamine, nonamethylenediamine and decamethylenediamine.

[0057] The allyl compound in the allyl-modified maleimide resin is at least one of diallyl bisphenol A, diallyl bisphenol S, allyl phenoloxy resin, allyl phenol-formaldehyde resin and diallyl diphenyl ether.

[0058] Specifically, the modified maleimide resin is selected from any one or more of the following brands of materials: BMI-1000, BMI-1000H, BMI-1100, BMI-1100H, BMI-2000, BMI-2300, BMI-3000, BMI-3000H, BMI-4000H, BMI-5000, BMI-5100, BMI-7000, BMI-7000H manufactured by Yamato Chemical Industry Co., Ltd.; BMI, BMI-70, BMI-80 manufactured by KI Chemical Industry Co., Ltd. of Japan; MIR-3000, MIR-5000 manufactured by Nippon Kayaku Co., Ltd.; X9-450, X9-470 manufactured by DIC Corporation of Japan; D936, D937, D939, D950 manufactured by Sichuan Dongcai Co., Ltd.

[0059] In the resin composition of the present invention, the content of epoxy resin is 0-60 parts by weight. It is known that when the content of epoxy resin is 0, that is, the resin composition does not contain the epoxy resin. When the content of epoxy resin is greater than 0, that is, the resin composition contains the corresponding parts by weight of epoxy resin. That is, the content of epoxy resin in the resin composition of the present invention can be 0 parts by weight, 10 parts by weight, 20 parts by weight, 30 parts by weight, 40 parts by weight, 50 parts by weight, 60 parts by weight and specific point values ​​between the above values. Due to space limitations and considerations of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0060] Preferably, the content of the epoxy resin is 10 to 40 parts by weight, that is, the content of the epoxy resin can be 10 parts by weight, 20 parts by weight, 30 parts by weight, 40 parts by weight and specific points between the above values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the range.

[0061] In some optional embodiments, the epoxy resin is selected from at least one of the following structures:

[0062] Wherein, p is an integer from 1 to 20;

[0063] Wherein, n is an integer from 1 to 20;

[0064] Wherein, m is an integer from 0 to 20;

[0065] Wherein, n is an integer from 1 to 20; Wherein, n is an integer of 1-20.

[0066] Specifically, the epoxy resin can be selected from at least one of HP4032, HP4032H, HP4032D, HP4032SS, HP4700, HP4710, N-690, N-695, HP7200, HP7200H, HP7200HH, EXA7311, HP6000 manufactured by DIC, NC3000, NC7000, NC3100 manufactured by Nippon Kayaku, ESN475V, ESN485 manufactured by Nippon Steel Chemical, etc.

[0067] Furthermore, the resin composition further comprises 0.01-8 parts by weight of a catalyst, wherein the catalyst is at least one selected from imidazoles, pyridines, organic phosphorus or metal salts.

[0068] Preferably, the imidazole catalyst is selected from at least one of 4-dimethylaminopyridine, 2-methylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, modified imidazole and zinc octanoate.

[0069] Preferably, the organophosphorus is selected from triphenylphosphine.

[0070] Furthermore, the resin composition also contains 5-60 parts by weight of a flame retardant, so that the final cured product has a certain flame retardant effect.

[0071] The flame retardant is selected from at least one of a bromine flame retardant, a phosphorus flame retardant, a nitrogen flame retardant, an organic silicon flame retardant, and an organic metal salt flame retardant.

[0072] Specifically, the bromine flame retardant is selected from decabromodiphenyl ether, decabromodiphenyl ethane, brominated styrene or tetrabromophthalamide. The phosphorus flame retardant is selected from inorganic phosphorus, condensed phosphate ester, phosphoric acid, hypophosphite, phosphorus oxide, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO), 10-(2,5-dihydroxyphenyl)-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO-HQ), (m is an integer from 1 to 5), 10-phenyl-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, tris(2,6-dimethylphenyl)phosphine, phosphazene, modified phosphazene.

[0073] In a preferred embodiment, the flame retardant is a condensed phosphate ester, a hypophosphite or a bis-DOPO compound.

[0074] Furthermore, the present invention also provides a use of the above resin composition in prepregs, copper-clad laminates, insulating films, insulating boards, circuit substrates and electronic devices.

[0075] Specifically, the present invention further provides a prepreg, which comprises a reinforcing material and the above-mentioned resin composition, wherein the resin composition is impregnated on the reinforcing material.

[0076] The reinforcing material may be selected from at least one of natural fibers, organic synthetic fibers, organic fabrics, and inorganic fabrics.

[0077] Preferably, the reinforcing material is glass fiber cloth. Among the glass fiber cloth, open fiber cloth or flat cloth is preferably used. More preferably, the glass fiber cloth is E glass fiber cloth, S glass fiber cloth, T glass fiber cloth or Q glass fiber cloth.

[0078] In addition, when the reinforcing material is glass fiber cloth, the glass fiber cloth generally needs to be chemically treated to improve the interface bonding between the resin composition and the glass fiber cloth. The main method of the chemical treatment is coupling agent treatment, and the coupling agent used is preferably epoxy silane coupling agent or amino silane coupling agent, so that the reinforcing material has good water resistance and heat resistance.

[0079] Specifically, the method for preparing the prepreg comprises the following steps:

[0080] Dissolving the resin composition with a solvent to prepare a resin composition glue solution;

[0081] The reinforcing material is immersed in the above-mentioned resin composition glue solution, and then the immersed reinforcing material is taken out and heated and dried to obtain the prepreg.

[0082] In a specific embodiment, the impregnated reinforcing material is baked at 100° C. to 180° C. for 1 min to 15 min, and the prepreg is obtained after drying.

[0083] Specifically, the solvent can be selected from at least one of acetone, butanone, methyl isobutyl ketone, N,N-dimethylformamide, N,N-dimethylacetamide, ethylene glycol methyl ether, propylene glycol methyl ether, benzene, toluene, xylene, and cyclohexane.

[0084] The present invention does not specifically limit the amount of solvent used in preparing the prepreg. The amount of solvent added is selected by those skilled in the art based on their own experience, as long as the obtained resin composition glue has a viscosity suitable for use.

[0085] The present invention also provides a copper-clad laminate, which comprises at least one of the above-mentioned prepregs and a metal foil formed on at least one side of the prepreg. When the copper-clad laminate comprises only one of the above-mentioned prepregs, the metal foil is arranged on at least one side of the surface of the prepreg. When the copper-clad laminate comprises at least two of the above-mentioned prepregs, the at least two prepregs are stacked and bonded together by heating and pressurizing to form a combined sheet, and then the metal foil is bonded on one side or both sides of the combined sheet by heating and pressurizing to form the copper-clad laminate.

[0086] Specifically, the preparation steps of the copper-clad laminate are as follows: a single side or double sides of a prepreg is coated with metal foil, or at least two prepregs are stacked to form a combined sheet, a single side or double sides of the combined sheet is coated with metal foil, and hot pressing is performed to obtain a copper-clad laminate.

[0087] The pressing conditions of the copper-clad laminate are: pressing at a pressure of 0.2 to 2 MPa and a temperature of 150° C. to 250° C. for 1 to 4 hours.

[0088] Specifically, the number of the prepregs can be determined according to the required thickness of the copper-clad laminate, and one or more prepregs can be used.

[0089] The metal foil may be copper foil or aluminum foil, and its material is not limited; the thickness of the metal foil is not particularly limited, such as 5 μm, 8 μm, 12 μm, 18 μm, 35 μm or 70 μm.

[0090] The present invention also provides an insulating plate, which comprises at least one of the aforementioned prepreg sheets.

[0091] The present invention also provides an insulating film, which comprises a carrier film and the aforementioned resin composition coated thereon, and can significantly improve the heat resistance of the insulating film.

[0092] The preparation method of the insulating film is as follows: dissolving the resin composition with a solvent to prepare a resin composition glue solution, then coating the resin composition glue solution on a carrier film, and heating and drying the carrier film coated with the resin composition glue solution to obtain the insulating film.

[0093] In a specific embodiment, the carrier film coated with the resin composition glue is baked at 100° C. to 160° C. for 3 min to 10 min, and the insulating film can be obtained after drying.

[0094] The solvent is selected from at least one of acetone, butanone, methyl isobutyl ketone, N,N-dimethylformamide, N,N-dimethylacetamide, ethylene glycol methyl ether, propylene glycol methyl ether, benzene, toluene, xylene and cyclohexane.

[0095] The carrier film is selected from at least one of PET film, PP film, PE film and PVC film.

[0096] The present invention also provides a circuit substrate, which includes one or more of the aforementioned prepreg, copper-clad laminate, insulating plate, and insulating film.

[0097] The present invention also provides an electronic device, which includes the aforementioned circuit substrate.

[0098] The content of the present invention will be described in detail below with specific embodiments; of course, it can be understood that the embodiments of the present invention are not limited to these embodiments.

[0099] Examples 1 to 5 and Comparative Examples 1 to 3:

[0100] The components and contents of the resin compositions of Examples 1 to 5 and Comparative Examples 1 to 3 are shown in Table 1 below:

[0101] Table 1

[0102]

[0103] Specifically, the information of each component involved in Table 1 above is shown in Table 2 below:

[0104] Table 2

[0105]

[0106]

[0107] The preparation method of the resin composition in Examples 1 to 5 and Comparative Examples 1 to 3 is as follows: according to the components and corresponding contents in Table 1, an appropriate amount of butanone is mixed, stirred and mixed, and then diluted to a resin composition glue having a solid content of 65wt%, wherein the solid content of 65wt% is calculated by weight.

[0108] The E glass fiber cloth 1078 used as a reinforcing material was pretreated with an epoxy silane coupling agent and then immersed in the resin composition glue obtained in the above-mentioned Examples 1 to 5 and Comparative Examples 1 to 3, taken out after infiltration, placed in a 160°C forced air drying oven, and baked for 3 to 6 minutes to obtain semi-cured sheets corresponding to Examples 1 to 5 and Comparative Examples 1 to 3, respectively.

[0109] Copper-clad laminates corresponding to the above-mentioned embodiments 1 to 5 and comparative examples 1 to 3 were prepared. The method for preparing the copper-clad laminate was as follows: two semi-cured sheets prepared as above were cut to 300×300 mm, and the two semi-cured sheets were stacked into a composite sheet with a certain stacking structure, and then a low-profile electrolytic copper foil with a thickness of 12 μm was placed on both sides of the composite sheet, and then placed in a vacuum hot press, and hot pressed for 1.5 hours at a pressure of 1.5 MPa and a temperature of 220°C to obtain a copper-clad laminate.

[0110] The copper-clad laminates corresponding to the above-mentioned embodiments 1 to 5 and comparative examples 1 to 3 were used to perform performance tests. Specifically, the performance evaluation method is as follows:

[0111] (1) Glass transition temperature (Tg): tested using a dynamic mechanical analyzer (DMA) according to IPC-TM-650 2.4.24.4;

[0112] (2) Thermal conductivity: tested using ASTM D5470-2017 method;

[0113] (3) Dk and Df: Dielectric properties at 10 GHz were measured using the plate method in accordance with IPC-TM-650 2.5.5.9;

[0114] (4) Peel strength: According to the "after thermal stress" experimental conditions in IPC-TM-650 2.4.8 method, the peel strength of the metal cover layer is tested;

[0115] (5) Internal substrate quality: The internal substrate quality was observed under a microscope. When there was no filler agglomeration or aggregation within an area of ​​300 mm × 300 mm, it was indicated as 0. When there were less than 5 filler agglomerations or aggregations, it was indicated as Δ. When there were more than 5 filler agglomerations or aggregations, it was indicated as ╳.

[0116] The properties of the copper-clad laminates obtained using the prepregs in Examples 1 to 5 and Comparative Examples 1 to 3 are shown in Table 3 below.

[0117] Table 3

[0118]

[0119] A parallel comparison is made between Example 2 and Comparative Example 2. It can be seen that compared with the conventional silica filler used in the resin composition in Comparative Example 2, Example 2 uses high Dk angular calcium titanate inorganic fillers of different shapes and high thermal conductivity spherical silicon nitride inorganic fillers in combination. The copper-clad laminate prepared from the resin composition in Example 2 has a higher dielectric constant and higher thermal conductivity, and can be well used in the field of high heat-resistant high-frequency antenna substrate modules, especially can meet the requirements of millimeter wave antenna modules.

[0120] Example 2 and Comparative Example 1 are compared in parallel. The fillers in Example 2 are angular calcium titanate and spherical silicon nitride of different shapes, while angular calcium titanate and angular boron nitride of the same shape are used in Comparative Example 1. Comparison of the performance test results shows that the copper-clad laminate prepared from the resin composition in Example 2 has a higher dielectric constant, higher peel strength, and better internal substrate quality, and can be well used in the field of high-heat-resistant high-frequency antenna substrate modules, especially meeting the requirements of millimeter-wave antenna modules.

[0121] Example 5 and Comparative Example 3 are compared in parallel. The fillers in Example 5 are calcium titanate and spherical silicon nitride with different shapes, while spherical strontium titanate and spherical silicon nitride with the same shape are used in Comparative Example 3. Comparison of the performance test results shows that the copper-clad laminate prepared from the resin composition in Example 2 has higher thermal conductivity, higher peel strength, and better internal substrate quality, and can be well used in the field of high-heat-resistant high-frequency antenna substrate modules, especially meeting the requirements of millimeter-wave antenna modules.

[0122] At the same time, the fillers in the above-mentioned Examples 1 and 3 use spherical strontium titanate and angular boron nitride of different shapes, and the average particle size of the spherical strontium titanate is smaller than the average particle size of the angular boron nitride; although the fillers in the above-mentioned Examples 2, 4, and 5 use angular calcium titanate and spherical silicon nitride of different shapes, the average particle size of the angular calcium titanate is larger than the average particle size of the spherical silicon nitride; by comparing their performance test results, it can be seen that the copper-clad laminates prepared from the resin compositions in Examples 1 and 3 have higher thermal conductivity and higher Dk value, and can be well used in the field of high heat-resistant high-frequency antenna substrate modules, especially can meet the requirements of millimeter wave antenna modules.

[0123] It can be seen that in the resin composition of the present invention, a first filler with high Dk (dielectric constant) and a second filler with high thermal conductivity are added to the high heat-resistant bismaleimide resin-cyanate ester curing system, and the first filler with high Dk (dielectric constant) is used in combination with the second filler with high thermal conductivity, so that the resin composition further improves the thermal conductivity and Dk value on the basis of meeting the higher heat resistance; at the same time, the first filler and the second filler are set to different shapes and used in combination with each other, which can increase the filling amount of the filler in the resin composition, inhibit the decrease in thermal conductivity and Dk value, and improve the peel strength, so as to obtain a resin composition with excellent high heat resistance, high Dk, high peel strength and high thermal conductivity, so that finally a cured product with high heat resistance, high thermal conductivity, high dielectric constant and high peel strength can be obtained, so as to obtain a cured product with relatively excellent comprehensive performance, which can be well used in the field of high heat-resistant high-frequency antenna substrate modules, especially can meet the requirements of millimeter wave antenna modules.

[0124] It should be understood that although this specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each implementation mode may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

[0125] The series of detailed descriptions listed above are only specific descriptions of feasible implementation methods of the present invention. They are not intended to limit the scope of protection of the present invention. Any equivalent implementation methods or changes that do not deviate from the technical spirit of the present invention should be included in the scope of protection of the present invention.

Claims

1. A resin composition, characterized in that include: Modified maleimide resin: 50-100 parts by weight; Cyanate compound: 5-50 parts by weight; Epoxy resin: 0-60 parts by weight; First filler: 10-100 parts by weight, wherein the Dk of the first filler at 10 GHz is greater than 10; Second filler: 1-150 parts by weight, the thermal conductivity of the second filler is greater than 15 W / mK; One of the first filler and the second filler is a spherical structure, and the other is a non-spherical structure.

2. The resin composition according to claim 1, characterized in that: The first filler is a titanate inorganic filler; or, the first filler is a titanate inorganic filler, and the titanate inorganic filler is selected from at least one of calcium titanate, strontium titanate, barium titanate, lead titanate, magnesium titanate, lead zirconate titanate, and lanthanum lead zirconate titanate.

3. The resin composition according to claim 1, characterized in that: The second filler is an inorganic nitride filler; or, the second filler is an inorganic nitride filler, and the inorganic nitride filler is selected from at least one of aluminum nitride, boron nitride, and silicon nitride.

4. The resin composition according to claim 1, characterized in that: The first filler is an inorganic filler surface-treated with a silane coupling agent; and / or the second filler is an inorganic filler surface-treated with a silane coupling agent.

5. The resin composition according to claim 1, characterized in that: The average particle size of the first filler is 0.1 μm-5 μm; the average particle size of the second filler is 3 μm-25 μm.

6. The resin composition according to claim 5, characterized in that: The average particle size of the first filler is smaller than the average particle size of the second filler.

7. The resin composition according to claim 1, characterized in that: The cyanate compound is selected from at least one of bisphenol A cyanate compounds, bisphenol F cyanate compounds, bisphenol E cyanate compounds, bisphenol M cyanate compounds, DCPD cyanate compounds, naphthalene cyanate compounds, biphenyl cyanate compounds, and triphenyl cyanate compounds.

8. The resin composition according to claim 1, characterized in that: The modified maleimide resin is at least one of an allyl-modified maleimide resin, an aromatic diamine-modified maleimide resin, an aliphatic diamine-modified maleimide resin, and an aminophenol-modified maleimide resin.

9. The resin composition according to claim 1, characterized in that: The epoxy resin is selected from at least one of the following structures: Wherein, p is an integer from 1 to 20; Wherein, n is an integer from 1 to 20; Wherein, m is an integer from 0 to 20; Wherein, n is an integer from 1 to 20; Wherein, n is an integer from 1 to 20.

10. Use of the resin composition according to any one of claims 1 to 9 in prepregs, copper-clad laminates, insulating films, insulating boards, circuit substrates and electronic devices.